Tibia Pathology and Fractures - Nikolopoulos, Dimitrios D.; Safos, George K.; Michos, John (IntechOpen, 2020)
The tibia is the larger, stronger, and anterior (frontal) of the two bones in the leg, which connects the knee with the ankle bones. The tibia, or shinbone, is the most fractured long bone in the body. In recent years, high-energy accidents result in comminuted tibia fractures or intraarticular fractures of the knee (plateau) or ankle (platform) that need immediate open reduction and internal fixation with anatomical plates or intramedullary nails. Intraarticular fractures with comminution or fractures with non-appropriate internal fixation predispose to post-traumatic knee or ankle arthritis. Conservative current therapies (injections of plate-rich plasma or stems cells) or high tibia osteotomies may delay the need of total knee arthroplasty. Tibia Pathology and Fractures analyzes all the up-to-date internal fixation or other operative or conservative therapies.